PENGARUH TERAPI FISIK DALAM MENGATASI KENAIKAN BERAT BADAN PADA AKSEPTOR KB HORMONAL - Miliana, Lidvina Ochyna Sari; Nyna Puspita Ningrum; Nina Hidayatunnikmah (Rena Cipta Mandiri, 2025)
Weight gain is a common side effect among hormonal contraceptive users, potentially leading to dissatisfaction, discontinuation, and long-term health risks. This study aimed to determine the effect of physical therapy in overcoming weight gain among hormonal contraceptive acceptors. This quantitative research employed a one-group pretest-posttest design, conducted at TPMB Affah Fahmi, Surabaya, in April–May 2023 with 31 respondents selected through purposive sampling. The intervention consisted of structured physical therapy sessions, three times a week for four weeks, involving aerobic exercise, stretching, and light strength training. Weight was measured before and after intervention, analyzed using paired t-test (p < 0.05). Results showed a significant decrease in average body weight from 57.44 ± 3.45 kg to 55.63 ± 3.26 kg (p = 0.000).